Examination of the Basics and Concepts of Deep Learning Networks and Object Detection for Tomato Detection - Mahyar Gohari Moghaddam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study examined the past studies, the advantages and disadvantages of each, and the history of algorithms and methods of object detection. Particularly, the studies on the detection of tomatoes and other agricultural products were examined as well. We then reviewed the proposed models and methods for object detection in the image, especially methods based on deep networks. Finally, we briefly compared some of the most widely used methods in this regard nowadays used by scholars and engineers in different problems in this field and examined the papers regarding the detection and localization of agricultural products, particularly tomatoes.